Difference in the plasma level of miR‐628‐3p in atopic dermatitis patients with/without atopic keratoconjunctivitis - Mayumi Ueta; Hiromi Nishigaki; Seitaro Komai; Chie Sotozono; Shigeru Kinoshita (Immunity, Inflammation and Disease)
Abstract Introduction Some but not all patients with atopic dermatitis (AD) present with allergic conjunctival disease (ACD) including severe types such as atopic keratoconjunctivitis (AKC) with/without giant papillae. We hypothesized that different factors are involved in the severity of ACD and AD. Recently we reported that hsa‐miR‐628‐3p could affect the balance of innate immunity by suppressing pathogen‐associated molecular patterns such as toll‐like receptor 3 (TLR3), RIG‐I, and MDA‐5. We also reported that TLR3 positively regulates ocular surface‐ and skin inflammation such as contact dermatitis and AD. Here we compared the plasma level of miR‐628‐3p in AD patients with severe AKC with giant papillae and/or shield ulcers, with the level in healthy controls and AD patient without AKC or with very mild AKC. Methods We used the plasma from 32 AD patients with severe AKC, from 40 healthy controls, and from 23 AD patient without AKC or with very mild AKC without giant papillae nor shield ulcers. Quantitative microRNA PCR assays were used to measure their plasma level of miR‐628‐3p. Results We found that plasma miR‐628‐3p was upregulated in AD with severe AKC, but not in severe AD without severe AKC, nor in our healthy controls. Conclusion Our new findings suggest that the plasma miR‐628‐3p level may represent a marker to predict the presence of severe AKC in AD patients.